2007
DOI: 10.1007/s12072-007-9034-1
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive predictors of large varices in patients hospitalized with gastroesophageal variceal hemorrhage

Abstract: Cirrhosis with HCC, clinical splenomegaly, hemodynamic instability, a previous history of GEVH, thrombocytopenia (i.e., platelet count <91,000), and splenic size >/=158 mm are independent noninvasive predictors of large varices in patients hospitalized with gastroesophageal variceal hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
4
17
0
Order By: Relevance
“…This study reported a mortality reduction to 7.5% with better monitoring. At our center, survival was over 90% in the pre-BCU and BCU data; similar results have been reported in other and our previous studies [10,22,23]. However, a trend of improvement in survival was observed in BCU data of 2007 up to 97%.…”
Section: Discussionsupporting
confidence: 90%
“…This study reported a mortality reduction to 7.5% with better monitoring. At our center, survival was over 90% in the pre-BCU and BCU data; similar results have been reported in other and our previous studies [10,22,23]. However, a trend of improvement in survival was observed in BCU data of 2007 up to 97%.…”
Section: Discussionsupporting
confidence: 90%
“…This in contrary to other studies where the IHM rate 8.7% is consistent with the experience from other centers. 28 Similar decline in the IHM rate has been reported in other studies. 29 The variation of the IHM for cirrhotic patients with variceal hemorrhage is likely related to the degree of underlying liver dysfunction, the use of life support systems such as blood, vasoactive agents, and endotracheal intubation, and the subsequent development of clinical complications including renal insufficiency, cardiopulmonary complications, and infection.…”
Section: Articlesupporting
confidence: 85%
“…30 Although IHM in cirrhotic patients with GI bleeding is declining 31,32 it is still associated with significant morbidity and mortality. 26,28 More than half of patients with GI bleeding have a comorbid disease mainly hypertension, diabetes mellitus, coronary artery diseases, and malignancies. 31 Clinical guidelines published in 2008 in Scotland cited a mortality rate of 4% in GI bleeding patients without comorbidities, with the mortality rate increasing 1.8 times in cases with heart failure, 3.8 times in cases with malignancy, and 2.0 times in cases with liver disease.…”
Section: Articlementioning
confidence: 99%
“…9 It is also a common cause of mortality amongst Pakistani population 10 and frequent cause of admission in our hospitals. 11 Portal hypertensive gastropathy is defined by mucosal and submucosal vascular ectasia in the absence of Inflammation. A lot of reasons counting modification in blood circulation in the spleen, humoral aspects and confined dysregulation of vascular quality have been concerned in the pathophysiology.…”
Section: Discussionmentioning
confidence: 99%